The stress level of craftsmen working in production division of PT Sony Central Industry, Jepara - Sri Hindriyastuti; Stefanus H; Syahrial Aman (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Background:The furniture industry is one of the trade sectors that continues to experience an increase. Industry requires craftsmen to improve the quality of their work in producing goods. This resulted in an increasingly heavy workload of craftsmen, especially the production of this condition, triggering work stress. In Jepara there were 4255 cases of work stress in 2019. Apart from that, during interviews with several craftsmen, information was obtained that in a day the number of products produced was adjusted to the number of orders received. If enough orders are received, the craftsmen have to work overtime for 2 hours after the work time to meet expected targets. Therefore, there is an increase in workload, thereby increasing the stress level of workers Methods and Purpose of Research: Using quantitative descriptive methods. This research was conducted on April 14 – 16, 2020 using a total sampling methods of 40 respondents. The data used is primary data with a single variable, namely the level of stress. Data analysis using descriptive statistical tests. It aims to find out the level of stress of the craftsmen in the production section of Sony Sentral Industry Jepara Regency in 2020.Results:The results showed that of the 40 most respondents the most stress level respondents were at moderate stress levels with 13 respondents (32.5%) and the lowest at mild stress levels of 5 respondents (12.5%).